2020
DOI: 10.1021/acs.biomac.0c00543
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradable Hydrogels for Rapid Screening, Isolation, and Genetic Characterization of Bacteria with Rare Phenotypes

Abstract: Screening mutant libraries (MLs) of bacteria for strains with specific phenotypes is often a slow and laborious process that requires assessment of tens of thousands of individual cell colonies after plating and culturing on solid media. In this report, we develop a three-dimensional, photodegradable hydrogel interface designed to dramatically improve the throughput of ML screening by combining high-density cell culture with precision extraction and the recovery of individual, microscale colonies for follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…As reported previously 19 , it was observed that cell density of 7.26 × 10 7 CFU/mL in the crosslinking buffer correlates to a density of ~ 90 cells/mm 2 encapsulated across the hydrogel. The prepared hydrogel can be incubated in media for culture.…”
Section: Hydrogel Formationsupporting
confidence: 81%
See 3 more Smart Citations
“…As reported previously 19 , it was observed that cell density of 7.26 × 10 7 CFU/mL in the crosslinking buffer correlates to a density of ~ 90 cells/mm 2 encapsulated across the hydrogel. The prepared hydrogel can be incubated in media for culture.…”
Section: Hydrogel Formationsupporting
confidence: 81%
“…The separation process in both formats has been successfully used to isolate bacteria that display unique growth behavior for downstream genotyping after culture and microscopic observation, a critical capability for connecting cell genotype to phenotype. To date, genomic characterizations of bacteria extracted from these interfaces have included 16S amplicon sequencing to identify multi-species collections of bacteria from environmental microbiomes that generate emergent growth behavior 18 , and for whole-genome sequencing to successfully identify genetic mutations that cause rare growth profiles in cells present within mutant libraries 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,[17][18][19] Hydrogel microspheres are widely used for microbial cell protection against the harsh conditions of reaction media such as variable temperature, pH and shear stress. 10,20 Moreover, hydrogel microspheres provide an excellent solution for cell culture and lineage, due to their large surface area, small regular shape, and extensive adjustability. 12,19,21 A single hydrogel microsphere can be used for capturing of single or few cells followed by monitoring of growth and phenotypic characterization.…”
Section: Introductionmentioning
confidence: 99%